Two and a half years on: data and experiences establishing a 'Virtual Clinic' for joint replacement follow up. Issue 7 (27th June 2018) - Lovelock, Thomas; O'Brien, Michael; Young, Ian; Broughton, Nigel
Abstract : Background: We use a 'Virtual Clinic' for follow up of hip and knee replacement patients. The aim of this study was to investigate patient compliance, pain and function, revision rates and surgeon experience using this system. Methods: All hip and knee replacements conducted from 2000 onwards were suitable for 'Virtual Clinic' review. Between July 2014 and December 2016, all patients due for follow up (at 1, 5 and 7 years post‐operatively, or biennially thereafter) were mailed an Oxford Hip or Knee Score and a request for a radiograph. A surgeon reviewed the questionnaire and radiograph and decided whether face‐to‐face review was necessary. We calculated compliance as the percentage of eligible patients who completed the 'Virtual Clinic'. We used retrospective review of medical records for all clinic participants to analyse Oxford scores, disposition following appointment, and revision rates. We reviewed all clinic participants in December 2017 to identify any further revisions. Surgeon feedback was assessed by emailed survey. Results: A total of 2076 patients were due for follow up. 1405 patients were contactable, and 710 completed the process. We calculated a 36% compliance rate. Surgeons decided 162 (23%) patients with a mean Oxford score of 24.2 required face‐to‐face assessment. This identified 13 patients needing revision. One other patient was revised for loosening which developed between 'Virtual Clinic' appointments. Surgeon feedback indicated the inclusion of a 'comment' section on the questionnaire as particularly useful. Discussion: We describe our adoption of a 'Virtual Clinic' for joint replacement follow up. We recommend this system as a practical method of following up patients.